(untitled) (Annals of Medical Research, 2024)
Aim: Developmental Hip Dysplasia (DDH) refers to a set of abnormalities involving the developing hip. These abnormalities range from mild instability to overt dislocation of the joint. It is important to treat this condition effectively to promote normal development of the hip and achieve good long-term results. Surgical and non-surgical methods are available as treatment methods. Closed reduction and casting in the "human position" under general anesthesia under operating room conditions are effective methods for DDH patients who fail with non-surgical methods. The purpose of this article is to share the clinical and radiological results of the patients we treated with closed reduction and casting in our clinic. Materials and Methods: Radiological and clinical evaluation of 176 hips of 117 patients who applied to İnönü University Faculty of Medicine Department of Orthopedics and Traumatology between January 2010 and October 2017 and were treated with closed reduction and pelvipedal casting was performed retrospectively. Results: The average preoperative acetabular index of the operated hips was 35.88 degrees, and the final follow-up acetabular index values were 22.09 degrees. Avascular necrosis was detected in 2 of the patients (1.7%). According to the modified McKay classification, very good results were obtained in 105 (90%) of 117 patients followed for closed reduction, good results were obtained in 11 (9%), and fair results were obtained in 1 (0.85%). Conclusion: Closed reduction and cast treatment in developmental hip dysplasia is an effective treatment method due to its low complication rate and high success rate in the appropriate patient group.